A determinação do ácido cianídrico em mandiocas (Manihot esculenta Crantz) por difusão - Franco Feitosa Teles, Francisco; Toledo de Oliveira, Tânia; Goreti de Almeida, Maria; da Silveira, Américo José; Martins Batista, Cid; Martins Rezende, Jorge Luiz (Revista Ceres, 2025)
A new method for the determination of hydrocyanic acid (HCN) in cassava roots, using Conway diffusion cells, was developed. Photometric measurements were carried out by the use of the Teles reagent at 540 nm.